Isolation and Characterization of Quercetin from Hydroalcoholic extract of Hibiscus cannabinus Linn Leaves - Thorat, Dattatraya B; Narwane, Sandeep; Kunkulol, Rahul (Research Journal of Science and Technology, 2025)
Herbal medicine is making a dramatic comeback as the side effects of synthetic medicine are daunting and the therapeutic approach is drifting towards substituent medicine. Quercetin is a plant pigment of flavonoid. It's found in many plants and foods, such as red wine, onions, green tea, apples, and berries. Quercetin has antioxidant and anti-inflammatory effects that might help reduce swelling, kill cancer cells, control blood sugar, and help prevent heart disease. Hibiscus cannabinus Linn., Leaves (Malvaceae) is an endangered plant species occurring in the Ahmednagar district (Maharashtra), India. Leaves are used in the treatment of antibilious, antioxidant, aphrodisiac, poultice and purgative. Fraction of hydroalcoholic extract of Hibiscus cannabinus Linn., Leaves by column chromatography was done. During the column elution process, the fractions 15 - 30 have a single banding pattern which was confirmed by TLC study. Phytochemical screening showed the presence of Flavonoids, Phenolic and Tannins. Physical and chemical tests of isolated compound were conducted. By using HPTLC, FTIR, 1H-NMR and GC-MS spectra of the isolated compound was confirmed as Quercetin.